Relationship among Foreign Direct Investment, Economic Growth and CO2 Emission: A Panel Data Analysis - Shaari, Mohd Shahidan; Hussain, Nor Ermawati; Abdullah, Hussin; Kamil, Syahida (International Journal of Energy Economics and Policy, 2014)
This study aims to investigate the effects of foreign direct investment and economic growth on CO2 emission. The panel data for the period of 1992 to 2012 from 15 developing countries were collected. The Johansen co-integration was conducted and the results show that there is co-integrated relationship between the variables (FDI, CO2 and GDP). Then the FMOLS was done and it was found that in the long run foreign direct investment does not have any effect on CO2 emission. Therefore, it suggests that an increase in FDI does not influence CO2 emission. However an increase in economic growth can intensify CO2 emission. Therefore, the developing countries should formulate policies on the environment in order to accomplish economic sustainability. At last, Granger causality based on VECM was employed and the results suggest there is no effect of FDI and GDP on CO2 emission in the short run. Keywords: CO2 emissions; economic growth; foreign direct investment JEL Classifications: Q4; Q5